Poverty and Unemployment in Stephen Crane’s Maggie: A Girl of the Streets: A New-Historicism Study - Krisna Sujiwa; Salsabila Bunga Sangsthita; Pandu Wiguna Restu (Universitas Gadjah Mada, 2023)
This paper will analyze poverty and unemployment in America that is portrayed in Maggie: A Girl of the Streets and the parallels connection between the story and the era in the US at that time. The researchers apply the Neo-Historicism approach to analyze the issue since it helps the researcher answer the research problem by analyzing the historical event, social problem, time and place that become key components. The researcher also employed a qualitative descriptive method to analyze the primary data, that is the novel by Stephen Crane entitled Maggie: A Girl of the Streets, while the supporting data were taken from books, articles, journals, online sources, and other sources. The outcome demonstrates the existence of societal problems like unemployment and poverty, which Stephen Crane makes the novel's primary problem. Researchers discovered a resemblance between Maggie's poverty and unemployment and the historical period in the USA at the time. What Crane shows in his novel is that not all Americans, especially those in New York during the industrial revolution, have happy lives. Moreover, a large number of people experience unemployment and poor condition, which is made worse by the industrial revolution and the American Panic of 1893. These issues resemble the societal issues that are presented in the book.